Design of Light-Sensitive Triggers for Endothelial NO-Synthase Activation - Sébastien Dilly; Linda J. Roman; Nicolas Bogliotti; Juan Xie; Eric Deprez; Anny Slama-Schwok (MDPI AG, 2020)
A specific light trigger for activating endothelial Nitric Oxide-Synthase (eNOS) in real time would be of unique value to decipher cellular events associated with eNOS activation or to generate on demand cytotoxic levels of NO at specific sites for cancer research. We previously developed novel tools called nanotriggers (NT), which recognized constitutive NO-synthase, eNOS or neuronal NOS (nNOS), mainly via their 2’ phosphate group which is also present in NADPH in its binding site. Laser excitation of NT1 bound to eNOS triggered recombinant NOS activity and released NO. We recently generated new NTs carrying a 2’ or 3’ carboxylate group or two 2’ and 3’ carboxylate moieties replacing the 2’ phosphate group of NADPH. Among these new NT, only the 3’ carboxylate derivative released NO from endothelial cells upon laser activation. Here, Molecular Dynamics (MD) simulations showed that the 3’ carboxylate NT formed a folded structure with a hydrophobic hub, inducing a good stacking on FAD that likely drove efficient activation of nNOS. This NT also carried an additional small charged group which increased binding to e/nNOS; fluorescence measurements determined a 20-fold improved affinity upon binding to nNOS as compared to NT1 affinity. To gain in specificity for eNOS, we augmented a previous NT with a “hook” targeting variable residues in the NADPH site of eNOS. We discuss the potential of exploiting the chemical diversity within the NADPH site of eNOS for reversal of endothelial dysfunction in cells and for controlled generation of cytotoxic NO-derived species in cancer tissues.